2020
DOI: 10.3389/fpls.2020.00241
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biological Functions of Thick Pili in the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: Cyanobacteria have evolved various strategies to sense and adapt to biotic and abiotic stresses including active movement. Motility in cyanobacteria utilizing the type IV pili (TFP) is useful to cope with changing environmental conditions. The model cyanobacterium Synechocystis sp. PCC 6803 (hereafter named Synechocystis) exhibits motility via TFP called thick pili, and uses it to seek out favorable light/nutrition or escape from unfavorable conditions. Recently, a number of studies on Synechocystis thick pili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Synechocystis has also been reported to produce conductive filaments under conditions of CO 2 limitation (Gorby et al, 2006), although whether these are Tfp is unclear. For detailed reviews of Tfp structure, biogenesis, and function in Synechocystis, see Schuergers and Wilde (2015) and Chen et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Synechocystis has also been reported to produce conductive filaments under conditions of CO 2 limitation (Gorby et al, 2006), although whether these are Tfp is unclear. For detailed reviews of Tfp structure, biogenesis, and function in Synechocystis, see Schuergers and Wilde (2015) and Chen et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…PCC6803 (hereafter Synechocystis) does not possess flagella. Instead, Synechocystis possesses pili that mediate cell motility required for adherence, biofilm formation and locomotion 8 . This system resembles the flagellar signal transduction pathway and has been extensively studied in Pseudomonas aeruginosa 9 .…”
mentioning
confidence: 99%
“…However, this needs experimental validation. Additionally, it has been suggested that the outer membrane pore-forming secretin PilQ, through which the DNA is translocated into the periplasm, may directly be involved in DNA binding [ 44 ].…”
Section: The Molecular Basis Of Natural Competencementioning
confidence: 99%
“…Once the DNA has been pulled into the periplasm, one DNA strand is degraded whilst the other is translocated further across the cytoplasmic membrane through the action of ComAEF [ 1 , 16 , 44 ]. In cyanobacteria, the exact function of each of these proteins is poorly understood.…”
Section: The Molecular Basis Of Natural Competencementioning
confidence: 99%
See 1 more Smart Citation